Penerapan Undang-Undang Perkawinan di Desa Kec. Marindal 1 Gang. Baru Kabupaten Deli Serdang - Dewi Robiyanti (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Amendments to Law No. 1 of 1974 through Law No. 16 of 2019 equalize the minimum age of marriage for men and women to 19 years. Observations in the Village of Marindal 1 Gang Baru District were conducted to assess the implementation of this regulation. Data collection was conducted through direct observation and informal interviews with community leaders, parents, and adolescents. Data were recorded and analyzed qualitatively to identify the level of compliance with the minimum age of marriage according to Law No. 16 of 2019 concerning marriage. The results showed that some people already understand the rules, but there are still practices of underage marriage. Therefore, it is necessary to strengthen legal socialization and administrative supervision so that regulations are effective in preventing child marriage. The implementation of Law No. 16 of 2019, an amendment to Law No. 1 of 1974 concerning marriage in the Village of Marindal 1 Gang Baru District, has been optimal and the trend of child marriage has decreased. Ongoing legal education, strengthening the role of village governments, and administrative oversight are still needed to reduce the number of child marriages